Relevansi Kebijakan Salary Policy Pada Dosen Pegawai Negeri Sipil di Kementerian Pendidikan, Kebudayaan, Riset dan Teknologi Republik Indonesia dengan Realitas Sosial dan Perubahan Zaman - Syukron, Nurkholis; Irawan, Andri (Jurnal Administrasi Karya Dharma, 2024)
Education is one of the most important components in supporting the life of the nation and state. Education in Indonesia is guaranteed by the 1945 Constitution of the Republic of Indonesia which is explicitly stated in the phrase "educating the nation's life". The implementation of higher education in Indonesia has a number of complex dynamics, one of which is about the relevance of the income of Lecturers to PNS status which is less relevant to social status and changing times. This research is a descriptive research with a qualitative approach. The use of qualitative descriptive methods is carried out in order to comprehensively reveal and understand various phenomena that occur in order to obtain a clearer picture of the aspect being studied. Based on the results of the study, it can be seen that the salary system that has been accepted by lecturers with civil servant status can still be categorized as not meeting the eligibility instruments for living lecturers and their families. This happens because the amount of income received by lecturers with civil servant status has no relevance to the social reality that considers the lecturer profession as one of the elite professions in Indonesia but its income is still inferior to other professions.